Raffle's Views on Islam in Indonesia and Abdullah Bin Abdul Kadir's Observation on The British Colonialists - Tholib, Udjang (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 1999)
Dalam bentuk scan